If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the second equation is substituted into the first equation.
3x + 2y = -21
x - 3y = 4
Choose one answer. a. 3(3y + 4) + 2y = -21
b. 3(-3y + 4) + 2y = -21
c. 3x + 2(3y + 4) = -21
d. 3x + 2(-3y + 4) = -21
.

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Looking for something else?

Not the answer you are looking for? Search for more explanations.